Application Analysis of GPS Surveying and Mapping Technology in Engineering Surveying and Mapping - Jiang, Shexiang; Zhao, Bao (Journal of Theory and Practice of Engineering Science, 2023)
As a new modern technology, GPS technology has achieved good applications in multiple fields of modern social and economic development, and is constantly expanding its application scope. At the same time, it also provides strong guarantees for the quality and efficiency of work in different fields. The application of GPS technology in engineering surveying and mapping has many advantages compared to traditional surveying and mapping techniques in the past. It not only has high accuracy in surveying and mapping, but also has a relatively simple operation, requiring low proficiency of surveying and mapping technicians. Therefore, GPS surveying and mapping technology has been increasingly applied in engineering surveying and mapping. Therefore, we should pay attention to the application of GPS surveying technology in engineering surveying, continuously improve its surveying quality and efficiency, and promote the healthy and stable development of engineering construction.